2016
DOI: 10.1051/matecconf/20167801042
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Thermal Behavior for Natural Fibres Reinforced Epoxy using Thermogravimetric and Differential Scanning Calorimetric Analysis

Abstract: Abstract. This paper presented the research works on the investigation of the thermal behavior of the natural fibres; i.e. pineapple leaf fibre, kenaf fibre and mengkuang fibres reinforced epoxy. The thermogravimetric analysis and differential scanning calorimetric analysis were used to measure the thermal behavior of the treated and untreated pineapple, kenaf and mengkuang fibres reinforced epoxy. The samples for both analysis were subjected to maximum temperature 600°C at the heating rate of 10°C/min. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…These three ranges of decrease in mass for several natural fiber-epoxy composites have been reported before [10,23,24]. FA Fauzi et al divided the weight loss process of natural fiber-epoxy composites into two stages: (1) weight loss happened due to the vaporization from the fiber, (2) the weight loss due to decomposition of cellulose at 265 to 595 °C [25]. Comparing to our results, the weight loss in stage (2) should be a combination of fiber and epoxy decomposition.…”
Section: Tg/dtg Analysismentioning
confidence: 65%
“…These three ranges of decrease in mass for several natural fiber-epoxy composites have been reported before [10,23,24]. FA Fauzi et al divided the weight loss process of natural fiber-epoxy composites into two stages: (1) weight loss happened due to the vaporization from the fiber, (2) the weight loss due to decomposition of cellulose at 265 to 595 °C [25]. Comparing to our results, the weight loss in stage (2) should be a combination of fiber and epoxy decomposition.…”
Section: Tg/dtg Analysismentioning
confidence: 65%
“…Fourier-transform infrared spectroscopy (FTIR) analysis revealed that mengkuang leaf contained the same functional group as found in natural fiber such as kenaf, jute and flax, suggesting its amazing potential as the reinforcing fiber [18]. Fauzi et al [19] found that the MLF was a good reinforcement in polyester.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its hydrophilic nature, natural fiber composites can cause several problems, such as swelling, dimension changes and voids [22]. To remove excessive content of hemicellulose, pectin, lignin and ash, alkaline treatment such as sodium hydroxide (NaOH) can be applied, which is a common surface treatment for MLF [19,23]. The clean surface of the fiber could significantly improve the adhesion between the fiber and matrix [24].…”
Section: Introductionmentioning
confidence: 99%